2013
DOI: 10.1364/boe.5.000312
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of subacute airway remodeling and adipose stem cell engraftment after airway injury

Abstract: Acquired airway injury is frequently caused by endotracheal intubations, long-term tracheostomies, trauma, airway burns, and some systemic diseases. An effective and less invasive technique for both the early assessment and the early interventional treatment of acquired airway stenosis is therefore needed. Optical coherence tomography (OCT) has been proposed to have unique potential for early monitoring from the proliferative epithelium to the cartilage in acute airway injury. Additionally, stem cell therapy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a randomized, placebo-controlled pilot study, ADSCs showed significant protective effects on ALI. Optical imaging analysis further revealed that they enhance subacute airway remodeling, and ameliorate ventilator-induced lung injury in rats (60). The major protective effects were attributed to eNOS and eNOS-derived NO (61).…”
Section: Adipose-derived Stem Cells (Adscs) In Lung Regenerationmentioning
confidence: 99%
“…In a randomized, placebo-controlled pilot study, ADSCs showed significant protective effects on ALI. Optical imaging analysis further revealed that they enhance subacute airway remodeling, and ameliorate ventilator-induced lung injury in rats (60). The major protective effects were attributed to eNOS and eNOS-derived NO (61).…”
Section: Adipose-derived Stem Cells (Adscs) In Lung Regenerationmentioning
confidence: 99%
“…In a randomized, placebo-controlled pilot study, ADSCs showed significant protective effects on ALI. Optical imaging analysis further indicated that they promote the subacute airway remodeling, and ameliorates ventilator-induced lung injury in rats [ 33 , 34 ]. The main protective reasons referred to eNOS and eNOS-derived NO [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, despite its frequent medical practices, how the transferred BM cells including stem cells and progenitors behave inside the bone marrow of the recipient at early time point after the BMT is not well understood yet [ 7 10 ]. Especially, our knowledge on the cellular-level behaviors of the transplanted BM cells which dynamically change over time after the BMT is relatively limited, which has been one of the limiting factors in previous efforts to improve the efficacy of BMT and to reduce the detrimental side effects [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%